Climate and job satisfaction in university environment. - Pecino-Medina, Vicente; Mañas-Rodriguez, Miguel A.; Díaz-Fúnez, Pedro A.; López-Puga, Jorge; Llopis-Marín, Juan-Manuel (Anales de Psicología / Annals of Psychology, 2015)
The aim of this paper is to determine the relationship between climate and job satisfaction in the context of a public university. Data were collected from 318 administrative and technical employees. Multilevel analyses were conducted to test the cross level effects of climate −occurring at a level of administrative areas− and individual job satisfaction. Kopelman, Brief and Guzzo’s (1990) model provides a theoretical framework to show the relationships between climate and cognitive and affective states, such as job satisfaction. Results show that climate in administrative areas has a significant and possitive effect on job satisfaction, which has important implications for the development of innovative practices of human resources that encourage the welfare and commitment of employees on the building of a healthy and socially responsible organization.